Evaluasi Sistem Manajemen Antrean Di Puskesmas Sindangkerta - Burhanudin, Irham Taufik; Hamdan, Hamdan (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Puskesmas is one of the health services whose traffic is difficult to determine, because it cannot be predicted that people will get sick and need health services. The queuing system at the puskesmas is implemented through several stages, namely the first stage the patient goes to the counter to get a queue number, after that the patient will be called according to the serial number to be served. This has a big impact on patients who were previously queuing because they have to be willing to wait longer to get service. This queue system often causes various kinds of problems and patient dissatisfaction. The Queue Management System at the Sindangkerta Community Health Center has several problems, including long queue waiting times which tend to be detrimental to patients who will receive services. Long queues cause longer waiting times. The queue is not easily accessible to prospective patients, making it difficult to obtain a queue number. This research uses qualitative research methods with a descriptive type. Data collection techniques using direct observation techniques, interviews and documentation. Data analysis techniques using data collection techniques, data reduction, data presentation and drawing conclusions. The results of the research show that the evaluation of the management of the queuing system at the Sindangkerta Community Health Center is quite good, but there are still problems, including long queue waiting times and difficulty for visitors to get a queue number.